2013
DOI: 10.3233/ves-130469
|View full text |Cite
|
Sign up to set email alerts
|

Validation of centrifugation as a countermeasure for otolith deconditioning during spaceflight: Preliminary data of the ESA SPIN study1

Abstract: In the framework of further space exploration, countermeasures to combat the drawbacks of human space flights are essential. The present study focuses on the influence of microgravity on the otolith-ocular reflex and aims to test the hypothesis of artificial gravity being an adequate countermeasure for the deconditioning of the aforementioned reflex. The so-called SPIN study, commissioned by the European Space Agency, can be considered as a control experiment in the broad sense for the Neurolab mission (STS-90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…57,69 Previous spaceflight studies have already shown that inter-subject variability in space travelers is quite high, also for other physiological processes such as sensorimotor adaptation 75,76 and vestibular and otolith deconditioning. 77,78 High inter-subject variability is therefore a feature that should be kept in mind when analyzing and interpreting spaceflight studies, in particular with regards to studies on spaceflight-induced neuroplasticity. Earth-based studies have already shown that neuroplasticity is a process that is highly individually dependent and is related to several factors such as demographics (e.g.…”
Section: General Difficulties and Limitations Of Space Researchmentioning
confidence: 99%
“…57,69 Previous spaceflight studies have already shown that inter-subject variability in space travelers is quite high, also for other physiological processes such as sensorimotor adaptation 75,76 and vestibular and otolith deconditioning. 77,78 High inter-subject variability is therefore a feature that should be kept in mind when analyzing and interpreting spaceflight studies, in particular with regards to studies on spaceflight-induced neuroplasticity. Earth-based studies have already shown that neuroplasticity is a process that is highly individually dependent and is related to several factors such as demographics (e.g.…”
Section: General Difficulties and Limitations Of Space Researchmentioning
confidence: 99%
“…Most of them belong to glycoproteins and function through the formation of receptor-ligand binding. The expression of cell adhesion proteins directly reflects the degree of adhesion between cells, or between cells and extracellular matrix [8]. Integrin is a heterodimeric transmembrane receptor composed of two subunits, α and β.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, centrifugation, close to 2× g, is also proposed as a countermeasure against the deleterious effects of microgravity seen in humans [33,34]. Therefore, before the exposure of humans to centrifugation, it is important to study its biological impacts.…”
Section: Introductionmentioning
confidence: 99%